Batik Millionaire: Kaleela by Azfa Enterprise / Anis Nurkhalidah Ahmad Fazil ... [et al.] - Ahmad Fazil, Anis Nurkhalidah; Nor Azman, Hanis Hasanah; Saipudin, Nurul Farisha; Azmin Sani, Siti Zulaiha; Hud, Syazarisya (2021)
As mentioned in the assignment requirements, to have a successful case study, we are required to analyze a real-life situation where existing problems need to be solved. Based on this statement, we intend to do some research while at the same time practice our knowledge skill on an actual company pertaining to the application of SWOT analysis and recommend on how to execute the alternatives suggested. Plus, due to the Covid-19 pandemic that we are facing right now, we take an alternative by doing an online interview in order to implement the Standard Operating Procedure (SOP) while at the same time we get information-rich and reliable information regarding the company. As for the research, we chose the Batik Millionaire that sells products related to women’s fashion where it is located at GM Klang. It was established in 2017 by Iffa Nadzirah binti Rahman in her early 20s and she determined her company’s vision as the best supplier with the cheapest price and their mission is to provide or supply products without labels to anyone who wants to start their own business. Foremost, from the interview, we can see the strengths, weaknesses, opportunities and threats of the company and form it on the diagram of SWOT and analyze it. Below is the concise of the SWOT analysis from the collected data during interview: • Strengths: their products have no expiry dates, led by strong founder • Weaknesses: their products have seasonal periods • Opportunities: they can get products cheaper and sell at reasonable prices since they are the supplier. • Threat: facing the unpredictable contract of the rent premise which will be kicked out once the contract expires. Apart from that, the major problems encountered by the Batik Millionaire could be classified as the inconsistencies which need to be improved by the Batik Millionaire in future. The problem includes lack of time management and inability to maintain an online presence. Yet, there are still solutions or alternatives that can solve the problems such as by hiring staff which helps for business management running smoothly, as well as applying scheduling systems to cover the lack of time management.